Cone beam computed tomography analysis of maxillary vestibular bone thickness in the esthetic region - Đurđević Milica; Bubalo Marija; Luković Ana; Igić Ana; Acović Aleksandar; Kanjevac Tatjana (Vojnosanitetski Pregled)
Background/Aim. Insufficient buccal bone thickness (thickness less than 2 mm) frequently leads to fenestration and dehiscence, and their consequences are additional bone resorption. That represents an additional problem during implant placement. Cone beam computed tomography (CBCT) is becoming a priority in the diagnosis of bone thickness needed for implant placement since it has proven to be an accurate and largely reliable diagnostic tool in the image of morphology and buccal wall thickness. The aim of this study was to measure the vestibular bone thickness of the anterior maxillary region in the Serbian population and compare the difference between men and women, as well as between the left and right sides of the jaw. Methods. CBCT images of 68 patients were examined from the existing database. The length from the cementoenamel junction to the beginning of the alveolar bone was measured, followed by the thickness of the vestibular bone at various clinically relevant locations. The data were statistically processed and analyzed. Results. A total of 373 teeth of the frontal region of the upper jaw, including 128 central incisors, 124 lateral incisors, and 121 canines, were analyzed. The thickness of the buccal bone in more than 88% of cases was less than 1.5 mm at all reference points, with mean values from 0.72 to 1.02 mm. Conclusion. A very small number of maxillary teeth have a vestibular bone thickness greater than 2 mm; therefore, the criterion to provide at least 2 mm of thickness needed for implant placement is difficult to meet. That increases the use of auxiliary methods of bone augmentation during immediate implant placement.